2005
DOI: 10.1002/cncr.21394
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma with noninflammatory skin involvement (T4b)

Abstract: BACKGROUNDIn this study, the authors evaluated the clinical presentation of patients with T4b breast carcinoma, analyzed the impact of noninflammatory skin involvement on long‐term survival, and addressed the question whether the T4 tumor category still has any justification.METHODSThe clinical course of a study group of 119 patients with skin involvement was compared with the outcome of a control group of 299 consecutive patients who had tumors of the same size but without skin involvement. All tumors were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In this study, we found that infiltration to the skin and chest wall (T4a-c) had a higher risk for distant metastasis particularly in the luminal A-like subtype although direct comparison of tumors larger and smaller than 5 cm did not show different risks of metastasis (Table 3 and 4). Although skin infiltration represents the extension of breast cancer, some studies did not show its direct impact on patients' survival and prognosis [38,39] rather than accompanied by axillary nodal infiltration [40].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that infiltration to the skin and chest wall (T4a-c) had a higher risk for distant metastasis particularly in the luminal A-like subtype although direct comparison of tumors larger and smaller than 5 cm did not show different risks of metastasis (Table 3 and 4). Although skin infiltration represents the extension of breast cancer, some studies did not show its direct impact on patients' survival and prognosis [38,39] rather than accompanied by axillary nodal infiltration [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Wieland et al (24) who noted that the 5-year survival rate for T4b, N0–3 patients <3 cm was 81% (95% CI 65–97%), which was also consistent with the 36–80% 5 year survival range (25) for all tumors classified as stage III at the time (26). More recently, in 2005 Guth and colleagues noted that in 119 patients, SI for breast tumors ≤5.0 cm had no effect on DSS compared to controls of similar sizes (8), and recommended completely abandoning the use of SI in staging outside of inflammatory carcinoma. They updated their findings a year later with similar results (27).…”
Section: Discussionmentioning
confidence: 99%
“…A few small studies have analyzed patients with T4b tumors, however they have all suggested that this subset of breast cancers has widely varied prognoses (38). Since cancer normally invades surrounding structures, logic suggests that a small invasive tumor that, by chance, arises close to skin and grows through it, does not necessarily have a worse prognosis than a similarly sized tumor arising and growing distant from skin.…”
Section: Introductionmentioning
confidence: 99%
“…Ten cases are event‐free survival, four cases alive with metastases; and one case had an 8‐year survival rate, with excellent quality of life. Numerous studies have observed a 5‐year survival of 36–67% in relation to the stage of the disease (2–6), taking into account that women over the age of 65 and operated for breast cancer die for reasons other than the disease (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the first breast carcinoma staging systems, at the beginning of the last century, cases with extension of tumor to the skin generally have been classified as locally advanced breast cancer (2). This historic significance of skin involvement was perpetuated in the current American Joint Committee on Cancer/International Union Against Cancer TNM staging system, in which noninflammatory breast carcinoma with direct extension to the skin also led to placement in the most unfavorable T category (T4) (3).…”
mentioning
confidence: 99%